Discrepancy in tidal deformability of GW170817 between the Advanced LIGO twin detectors - Tatsuya Narikawa; Nami Uchikata; Kyohei Kawaguchi; Kenta Kiuchi; Koutarou Kyutoku; Masaru Shibata; Hideyuki Tagoshi (Physical Review Research, 2019)
We find that the Hanford and Livingston detectors of Advanced LIGO derive a distinct posterior probability distribution of binary tidal deformability Λ[over ̃] of the first binary-neutron-star merger GW170817. By analyzing public data of GW170817 with a nested-sampling engine and the default TaylorF2 waveform provided by the LALInference package, the probability distribution of the binary tidal deformability derived by the LIGO-Virgo detector network turns out to be determined dominantly by the Hanford detector. Specifically, by imposing the flat prior on tidal deformability of individual stars, symmetric 90% credible intervals of Λ[over ̃] are estimated to be 527_{−345}^{+619} with the Hanford detector, 927_{−619}^{+522} with the Livingston detector, and 455_{−281}^{+668} with the LIGO-Virgo detector network. Furthermore, the distribution derived by the Livingston detector changes irregularly when we vary the maximum frequency of the data used in the analysis. This feature is not observed for the Hanford detector. While they are all consistent, the discrepancy and irregular behavior suggest that an in-depth study of noise properties might improve our understanding of GW170817 and future events.